2023
DOI: 10.3390/cancers15051572
|View full text |Cite
|
Sign up to set email alerts
|

Updated Clinical Evidence on the Role of Adipokines and Breast Cancer: A Review

Abstract: With the recent leaps in medicine, the landscape of our knowledge regarding adipose tissue has changed dramatically: it is now widely regarded as a fully functional endocrine organ. In addition, evidence from observational studies has linked the pathogenesis of diseases like breast cancer with adipose tissue and mainly with the adipokines that are secreted in its microenvironment, with the catalog continuously expanding. Examples include leptin, visfatin, resistin, osteopontin, and more. This review aims to en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 70 publications
0
13
0
1
Order By: Relevance
“…These results are in accordance with previous studies, in which circulating systemic inflammatory markers were found to be poor prognosis indicators in breast cancer patients. 34,35 Furthermore, we observed marked protective effects of anti-T. gondii IgG on breast cancer prognosis among women with a higher cytokine score than those with a lower score, a significant interaction (mainly contributed by IL-17 and IL-9). Patients with a high cytokine score might experience systemic inflammation, which induces angiogenesis, 36 a wellestablished driver of breast cancer aggressiveness and poor prognosis, 37 yet T. gondii infection inhibits angiogenesis.…”
mentioning
confidence: 69%
“…These results are in accordance with previous studies, in which circulating systemic inflammatory markers were found to be poor prognosis indicators in breast cancer patients. 34,35 Furthermore, we observed marked protective effects of anti-T. gondii IgG on breast cancer prognosis among women with a higher cytokine score than those with a lower score, a significant interaction (mainly contributed by IL-17 and IL-9). Patients with a high cytokine score might experience systemic inflammation, which induces angiogenesis, 36 a wellestablished driver of breast cancer aggressiveness and poor prognosis, 37 yet T. gondii infection inhibits angiogenesis.…”
mentioning
confidence: 69%
“…31 Research also indicated that adipokines were related to proliferation, invasion, and metastasis of breast cancer cells, and were also associated with the prognosis of breast cancer. 32 Moreover, it is important to note that breast cancer patients with liver metastasis exhibited drug resistance and eventually develop resistance to systemic chemotherapy, endocrine therapy, and targeted therapy. [33][34][35][36] Nevertheless, study had performed that the survival time for breast cancer patients with liver metastasis is only 4-8 months without treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account that 31.7% of our patients were diagnosed with HL (important predominance compared with the other diagnoses), along with the fact that there was an important activation of brown fat identified in these patients (high SUV max (LBM) values), we may consider that BAT could potentially play a role in the development of cancer itself. Preceding research reported that breast cancer has been associated with an increase in a variety of circulating BATokines [32]. These adipokines stimulate many pathways that aid in the development and hallmarks of this type of malignancy [32].…”
Section: Discussionmentioning
confidence: 99%
“…Preceding research reported that breast cancer has been associated with an increase in a variety of circulating BATokines [32]. These adipokines stimulate many pathways that aid in the development and hallmarks of this type of malignancy [32].…”
Section: Discussionmentioning
confidence: 99%